Happiness Is a Stochastic Phenomenon - Lykken, David; Tellegen, Auke (Psychological Science, 1996)
Happiness, or subjective well-being, was measured on a birth-record-based sample of several thousand middle-aged twins using the Well-Being (WB) scale of the Multidimensional Personality Questionnaire Neither socioeconomic status, educational attainment, family income, marital status, nor an indicant of religious commitment could account for more than about 3% of the variance in WB From 44% to 52% of the variance in WB, however, is associated with genetic variation Based on the retest of smaller samples of twins after intervals of 4 5 and 10 years, we estimate that the heriability of the stable component of subjective well-being approaches 80%